The IDENTITY OF PAIS IN MATTHEW 8:5-13: A RESPONSE TO JENNINGS AND LIEW’S ARTICLE ON MATTHEW 8:5-13 - Domocmat, Lowel (12th International Scholars Conference 2025, 2026)
This study critically examines the interpretation of the Greek word pais in Matthew 8:5–13, particularly in response to Jennings and Liew’s controversial claim that the term implies a pederastic relationship between the Roman centurion and his servant. Jennings and Liew argue that pais denotes a “boy-lover,” drawing on Greco-Roman military customs and classical sources, and suggest that Jesus’ healing of the pais without moral reprimand implies tacit acceptance of such a relationship. The author challenges this view by conducting a semantic and contextual analysis of pais in the Septuagint and New Testament. The study demonstrates that pais is variously used to mean “servant,” “child,” or “son,” depending on context, and never explicitly as a romantic or sexual partner. A comparison with the parallel Lukan account (Luke 7:1–10) further supports the interpretation of pais as a servant, as doulos and pais are used interchangeably. The author also critiques Jennings and Liew’s reliance on questionable historical analogies and highlights flaws in their assumptions about Roman military and social practices. He argues that the centurion's expression of unworthiness stems from cultural sensitivity to Jewish customs rather than hidden motives. The centurion’s faith, affirmed by Jesus as unparalleled in Israel, undermines the hypothesis of a concealed immoral relationship. Ultimately, the article concludes that pais in Matthew 8:5–13 should be understood as a valued servant and that Jennings and Liew’s reading is linguistically and contextually unfounded.